XFEM fracture analysis of composites - Mohammadi, S. (Soheil) (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2012)
"This book describes the basics and developments of the new XFEM approach to fracture analysis of structures and materials, providing state of the art techniques and algorithms for fracture analysis of structures. It offers numeric examples at the end of each chapter, as well as an accompanying website, which will include MATLAB resources, executables, data files, and simulation procedures of XFEM"--
Fracture Mechanics, A Review -- Extended Finite Element Method -- Static Fracture Analysis of Composites -- Dynamic Fracture Analysis of Composites -- Fracture Analysis of Functionally Graded Materials (FGMs) -- Delamination/Interlaminar Crack Analysis -- New Orthotropic Frontiers.
Includes bibliographical references and index.
Keywords: Composite materials -- Fracture; Composite materials -- Fatigue; Fracture mechanics; Finite element method; SCIENCE -- Mechanics -- General; TECHNOLOGY & ENGINEERING -- Material Science; Composite materials -- Fatigue; Composite materials -- Fracture; Finite element method; Fracture mechanics; Electronic books; Electronic books